1994
DOI: 10.1111/j.1439-0434.1994.tb04815.x
|View full text |Cite
|
Sign up to set email alerts
|

Interference Between Two Strains of Bean Common Mosaic Virus is Accompanied by Suppression of Symptoms Without Affecting Replication of the Challenging Virus

Abstract: An unusual type of interference between two strains of bean common mosaic virus, viz. NY15 and NL3, infecting bean plants, was investigatred. Wdhen a primary leaf was inoculated with NY15 as inducer and 1–8 days later, the opposite leaf with NL3 as challenger, the plant did not develop symptoms characteristic of NL3, i.e. systemic necrosis in the top, stem and wilting and withering of the youngest trifoloclate leaves. A7‐h interval between the inoculations with inducer and challenger already sufficed to reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 6 publications
1
10
1
Order By: Relevance
“…Although not a clear indicator of a role for xylem in systemic movement, localization of virus particles in the xylem has been reported in many instances (e.g. Dubois et al, 1994;Fribourg et al, 1987;Khan et al, 1994; Urban et al, 1989;Verchot et al, 2001). Further evidence supporting xylem transport has been reported in a few instances (Dubois et al, 1994;Opalka et al, 2000; Schneider & Worley, 1959a, b).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Although not a clear indicator of a role for xylem in systemic movement, localization of virus particles in the xylem has been reported in many instances (e.g. Dubois et al, 1994;Fribourg et al, 1987;Khan et al, 1994; Urban et al, 1989;Verchot et al, 2001). Further evidence supporting xylem transport has been reported in a few instances (Dubois et al, 1994;Opalka et al, 2000; Schneider & Worley, 1959a, b).…”
Section: Introductionmentioning
confidence: 87%
“…Xylem localization of virus particles has been reported for a number of viruses and hosts (e.g. Fribourg et al, 1987;Khan et al, 1994;Robertson & Carroll, 1989;Russo et al, 1967;Urban et al, 1989). Also, virus particles were recovered from guttation fluid in cucumber plants infected with 12 different viruses including CGMMV (French & Maureen, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…An unusual type of interference between mosaic-inducing strain NY15 of BCMV and necrosis-inducing strain NL3 of BBRV has been described [4]. It was demonstrated that plants of Phaseolus vulgaris 'Bataaf' inoculated first on one primary leaf with strain NY15, as inducer, and after one or more days on the opposite leaf, with strain NL3 as challenger, did not show symptoms characteristic of the latter strain, viz.…”
Section: Introductionmentioning
confidence: 98%
“…Histological studies on immunostained, thick sections of primary leaves, petiole and stem part between primary leaves and first trifoliolate leaf of doubly infected plants had shown that strain NL3 appeared later in the xylem of both petiole and stem, as compared with the singly inoculated control [4]. Such delayed appearance of NL3 in the xylem of stem parts of doubly infected plants might be due to either a lower viral content in these plant parts as a result of hampered transport from the primary leaves, or a different distribution of the virus in this part of the plant as compared to the singly inoculated controls.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation